Occupational Health and Safety Status of the Workers in the Garment Industry in Ghana - Thomas O. Asare; Abdul F. Ibrahim; Micheal Obeng Nyarko (Fashion and Textiles Review)
The clothing manufacturing industry is generally perceived as a safe place to work. Compared to other industries, there are relatively few serious accidents in clothing plants. The major health risks in this industry do not arise from immediate, potentially fatal hazards. Instead, the risks that clothing workers face are the types whose effect accumulates over time. This paper describes health and safety compliance level in the Ghanaian garment manufacturing industry. Qualitative research method was used to examine the nature of prevailing conditions at the garment manufacturing workshop with particular reference to safety environmental compliance in the Kumasi, Accra and Tema Metropolis. Interview and observation were employed to obtain data from respondents. Grounded theory analysis was employed in the data analysis. The study revealed that, sewing machine operators at the local industry show little concern about safety and healthy environmental compliance. Workers at the clothing industry were not bothered about the long-term effects regarding safety lapses at their job places. It was recommended that fashion design institutions, government agencies and the local garment associations should collaborate to organise training workshops for garment workers on safety and its related hazards.